C3 metabolism in ulcerative colitis and Crohn's disease. - Hodgson, H J (1977)
The metabolism of the third component of complement (C3) has been investigated in four patients with ulcerative colitis, three patients with Crohn's disease and seven control subjects, using radioiodinated C3 prepared from fresh human plasma. Both the fractional catabolic rate and synthesis rate of C3 were increased in the patients with inflammatory bowel disease, although the serum-C3 levels were normal or raised. The results suggest that complement activation may play a role in the pathogenesis of mucosal inflammation in these diseases.